Efficient mobilization of peripheral blood stem cells following CAD chemotherapy and a single dose of pegylated G-CSF in patients with multiple myeloma - Frühauf, Stefan; Klaus, Johanna; Hüsing, Johannes; Veldwijk, Marlon Romano; Buß, Eike Christian; Topaly, Julian; Seeger, Timon; Zeller, L.; Möhler, Thomas; Ho, Anthony Dick; Goldschmidt, Hartmut (Bone marrow transplantation, 2007)
High-dose chemotherapy followed by autologous blood stem cell transplantation is the standard treatment for myeloma patients. In this study, CAD (cyclophosphamide, adriamycin, dexamethasone) chemotherapy and a single dose of pegfilgrastim (12 mg) was highly effective in mobilizing peripheral blood stem cells (PBSCs) for subsequent transplantation, with 88% of patients (n = 26) achieving the CD34+ cell harvest target of > or = 7.50 x 10(6) CD34+ cells/kg body weight, following a median of two apheresis procedures (range 1-4) and with first apheresis performed at a median day 13 after CAD application (range 10-20). Patients treated with pegfilgrastim showed a reduced time to first apheresis procedure from mobilization compared with filgrastim-mobilized historical matched controls (n = 52, P = 0.015). The pegfilgrastim mobilization regimen allowed for transplantation of a median of 3.58 x 10(6) CD34+ cells/kg body weight while leaving sufficient stored cells for a second high-dose regimen and back-ups in most patients. Engraftment following transplantation was comparable to filgrastim, with a median time of 14 days to leucocyte > or =1.0 x 10(9)/l (range 10-21) and 11 days to platelets > or = 20 x 10(9)/l (range 0-15). The results of this study thus provide further support for the clinical utility of pegfilgrastim for the mobilization of PBSC following chemotherapy in cancer patients scheduled for transplantation.